Neurological, respiratory, musculoskeletal, cardiac and ocular side-effects of anti-PD-1 therapy. (June 2016) - Zimmer, Lisa; Goldinger, Simone M.; Hofmann, Lars; Loquai, Carmen; Ugurel, Selma; Thomas, Ioannis; Schmidgen, Maria I.; Gutzmer, Ralf; Utikal, Jochen S.; Göppner, Daniela; Hassel, Jessica C.; Meier, Friedegund; et al.
Abstract: Background: Anti-programmed cell death 1 (PD-1) antibodies represent an effective treatment option for metastatic melanoma and other cancer entities. They act via blockade of the PD-1 receptor, an inhibitor of the T-cell effector mechanisms that limit immune responses against tumours. As reported for ipilimumab, the anti-PD-1 antibodies pembrolizumab and nivolumab can induce immune-related adverse events (irAEs). These side-effects can involve skin, gastrointestinal tract, liver, the endocrine system and other organ systems. Since life-threatening and fatal irAEs have been reported, adequate diagnosis and management are essential. Methods and findings: In total, 496 patients with metastatic melanoma from 15 skin cancer centres were treated with pembrolizumab or nivolumab. Two hundred forty two side-effects in 138 patients have been analysed. In 77 of the 138 patients side-effects affected the nervous system, respiratory tract, musculoskeletal system, heart, blood and eyes. Not yet reported side-effects such as meningo-(radiculitis), polyradiculitis, cardiac arrhythmia, asystolia, and paresis have been observed. Rare and difficult to manage side-effects such as myasthenia gravis are described in detail. Conclusion: Anti-PD-1 antibodies can induce a plethora of irAEs. The knowledge of them will allow prompt diagnosis and improve the management resulting in decreased morbidity. Highlights: Anti-PD-1 antibodies can induce a plethora of immune-related adverse events (irAEs). irAEs of the nervous, musculoskeletal system, respiratory tract, heart, blood and eyes were analysed. Meningo-(radiculitis), polyradiculitis, cardiac arrhythmia, asystolia, and paresis were reported. If symptoms are autoimmune-related, prompt treatment has to be initiated to reduce morbidity. Since irAEs can start asymptomatic or with minimal symptoms, careful monitoring is essential.